Etiological and pathophysiological enigmas of severe coronavirus disease 2019, multisystem inflammatory syndrome in children, and Kawasaki disease - Jung-Woo Rhim; Jin-Han Kang; Kyung-Yil Lee (The Korean Pediatric Society, 2022)
During the coronavirus disease 2019 (COVID-19) pandemic, a novel multisystem inflammatory syndrome in children (MIS-C) has been reported worldwide since the first cases were reported in Europe in April 2020. MIS-C is temporally associated with severe acute respiratory syndrome coronavirus 2 infection and shows Kawasaki disease (KD)-like features. The epidemiological and clinical characteristics in COVID-19, KD, and MIS-C differ, but severe cases of each disease share similar clinical and laboratory findings such as a protracted clinical course, multiorgan involvement, and similar activated biomarkers. These findings suggest that a common control system of the host may act against severe disease insult. To solve the enigmas, we proposed the protein-homeostasis-system hypothesis in that every disease involves etiological substances and the host's immune system controls them by their size and biochemical properties. Also, it is proposed that the etiological agents of KD and MIS-C might be certain strains in the microbiota of human species and etiological substances in severe COVID-19, KD, and MIS-C originate from pathogen-infected cells. Since disease severity depends on the amounts of inflammation-inducing substances and corresponding immune activation in the early stage of the disease, an early proper dose of corticosteroids and/or intravenous immunoglobulin (IVIG) may help reduce morbidity and possibly mortality among patients with these diseases. Corticosteroids are low cost and an analogue of host-origin cortisol among immune modulators. This study's findings will help clinicians treating severe COVID-19, KD, and MIS-C, especially in developing countries, where IVIG and biologics supplies are insufficient.